Higher order thinking skills, metacoqnitive awareness and self-efficacy in reading comprehension among Pakistani ESL learners - Aziz, Musharraf (2023)
Effective reading comprehension relies on higher-order thinking and is crucial in this age of hyper-information and global communication. However, Pakistani ESL learners generally underperform in reading comprehension, but their higher order thinking skills (HOTS) and subskills have never been taxonomically modeled with diagnostic aims. In addition, studies on university learners’ higher order thinking skills (HOTS) are limited, and insufficient studies have investigated the moderating effects of metacognition and self-efficacy on the relationship between HOTS and reading performance. This study investigated Pakistani ESL learners’ HOTS in reading comprehension where Bloom’s taxonomy was used to model their strong and weak higher order thinking skills (HOTS). This study also evaluated the moderating effects of metacognitive awareness and self-efficacy on the relationship between HOTS and reading outcome. This study investigated Pakistani ESL learners’ HOTS in reading comprehension where Bloom’s taxonomy was used to model their strong and weak higher order thinking skills (HOTS). This study also evaluated the moderating effects of metacognitive awareness and self-efficacy on the relationship between HOTS and reading outcome. Under mixed-method research design, the quantitative data were collected from 200 learners using a tripartite reading test and two questionnaires while the qualitative data were gathered from six learners through think-aloud sessions. The quantitative data were descriptively and inferentially analyzed while the qualitative data were analyzed using thematic framework analysis. The findings revealed that the respondents’ three cognitive core processes and eight subprocesses of HOTS were weak. In processual skills, the respondents were deficient in analyzing texts, evaluating inconsistencies, and synthesizing textual input. Creating was the most contributive skill whereas Evaluating was the weakest skill. At subprocessual level, generating textual information was the strongest subskill whereas critiquing was the weakest subskill. Strategically, metacognitive awareness and self-efficacy significantly moderated the relationship between higher order thinking skills (HOTS) and reading performance. Apart from that, the qualitative analysis revealed deficiencies in the respondents’ textual analysis, inconsistency evaluation and information reconstruction. The learner skill model was similar in both genders however females outperform males in Creating skill while males outperform females in Analyzing and Evaluating skills. This study offers valuable implications for ESL teachers, learners, assessors, curriculum designers, washback strategists, policymakers and gender-specific institutions.